Aspects of shooting velocity in Norwegian elite team handball - Shaher, S. (Serbian Journal of Sports Sciences, 2014)
The aim of this study was to quantify differences in shooting velocity as a function of player position, age, shooting type and shot placement on goal. Seventy-four male elite handball players (age 22 ±3 yrs, height 187 ±7 cm, body mass 86 ±10 kg) were recruited. The athletes performed set shots, low arm shots and jump shots with a 2 m run-up in randomized order, and all shots were monitored by a radar speed gun. The results show that back players had significantly higher (p 21 years (85.0 ± 5.8 m•s-1). The results show that the set shot (86.8 ± 6.6 m•s-1) and the low arm shot (85.8 ± 6.0 m•s-1) had significantly higher velocity compared to jump shot (80.6 ± 5.5 m•s-1). No differences in shooting velocity were detected regarding shot placement (high vs. low) on the goal for either type of shooting. This study provides effect magnitude estimates for the influence of playing position, age, shooting type and ball shot placement on shooting velocity in male handball. High performance players achieve greater shooting velocities regardless of type of shooting and shot placement on goal. The ability to use varying shooting strategies is crucial in handball.